Fotossensibilização por Brachiaria ruziziensis em ovinos: avaliações clínica, patológica, micológica e fitoquímica por LC-MS/MS - Gabriella Matoso Lima Diamantino (2018)
Some species of the genus Brachiaria are cultivated worldwide in regions of tropical and subtropical climate as the main forage for ruminants. Several studies report hepatogenic photosensitization by Brachiaria decumbens, B. brizantha and B. humidicola, but Brachiaria ruziziensis has only been reported in Brazil by two studies. Cutaneous and hepatic lesions may be caused by the saponins present in the leaves or the mycotoxin sporodesmin produced by the saprophyte fungus Pithomyces chartarum. The present work aims to describe clinical and pathological changes in an outbreak of hepatogenic photosensitization caused by B. ruziziensis in sheep. In addition, it intends to offer subsidies to better understand the etiology of this photosensitization, through the evaluation of the steroidal saponin protodioscin and the spore count of P. chartarum. Crossbred Santa Inês sheep showed signs of photosensitization when fed a new clone of B. ruziziensis. Clinical signs included jaundice, apathy, dehydration and photosensitization, characterized by facial edema and cutaneous scars, especially in the ears. At necropsy of a dead animal, there was generalized jaundice, crustal lesions on the face and especially on the ears, the kidneys and liver were firm and greenish. Histologically, the liver had diffuse infiltrate of foamy macrophages, rare multinucleated cells, discrete volume increase of hepatocytes (megalocytosis) characteristic of histiocytic hepatitis with sharp diffuse sharp acute and skin macrophages, acute focally extensive epidermal and dermal necrosis accentuated with occlusive thrombi. The B. ruziziensis clone showed low levels of protodioscin (0.0200.024% in mature leaves and 0.0650.084% in sprouts) based on LC-MS/MS analysis and high spore counts of P. chartarum. Thus, it is likely that the photosensitization by B. ruziziensis described herein was caused by the mycotoxin sporidesmin